KINERJA AGRIBISNIS TEBU RAKYAT DI KABUPATEN PURBALINGGA - , Gilang Hanu Pramatatya ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objectives of this research are to analyze the influence of production factors toward the sugarcane farming production in Purbalingga Regency, to analyze the effect of input price of sugarcane production toward the net income of sugarcane farming, to know the criteria of sugarcane farming management, and to know the net income level of sugarcane farming. This research used analysis descriptive method and it was carriedout through gathering primary data with sugargane farmer as respondents. The field survey was done in Pengadegan District by using Purposive Sampling method in consideration of widest land area and the location of citizenry sugarcane farmers cooperative. Respondents were selected by Proportional Random Sampling method for farmers group member and Snowball Sampling method for non-group farmers. The data was analyzed by using: Cobb-Douglas production function, Cobb-Douglas profit function, R/C ratio, and net revenue analysis. The results showed that the addition of sugarcane seed, labor, and element P have a significant positive effect on the sugarcane production, while the addition of element N has a significant negative effect on sugarcane production. Besides, the sugarcane seed prices and the new planted system have significant negative effect on the net income of sugarcane farming, while the land area and farmer participation in the group have a significant positive effect on the net income of sugarcane farming. R/C ratio value for the new planted system is 1,196/cropping season, while the ratoon system is 2,176/cropping season. The average of net income with a new planted system is Rp8.184.984/hectare/ cropping season, while the ratoon system is Rp25.986.746/hectare/cropping season.